ON THE MECHANISM OF HEATING UP OF THE INDO-AUSTRALIAN PLATE - Verzhbitsky E.V.; Lobkovsky L.I. (My University, 1993)
Peculiarities of the tectonic structure and the distribution of geophysical fields in the Central Indian Basin are considered. On the basis of heat flow data, retrieved in the Central Indian Basin, the zone of intraplate deformations, the Indian shield area, and data obtained by the authors in the 20th cruise of R/V Ac. M. Keldysh in the Afanasy Nikitin seamount group area, the anomalous pattern of the geothermal field is discussed. The estimates performed lead us to belief that the mechanism of the additional heating up of the Indo-Australian plate lies in the generation of heat in the crustal serpentinite layer owing to the dissipation of mechanical energy after the two-level plate tectonics model, on the one hand, and to the exothermal reaction of serpentinization, on the other.